2017
DOI: 10.1016/j.wear.2017.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steel hardness on soot wear

Abstract: Due to incomplete combustion, high levels of soot can accumulate in engine lubricants between drain intervals. This soot can promote wear of engine parts such as timing chains and cam followers. One standard approach to reducing wear is to increase the hardness of the rubbing components used. According to the Archard wear equation, wear rate should be broadly inversely proportional to hardness. To explore this approach for controlling soot wear, wear tests have been conducted in a High Frequency Reciprocating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Carbon black may contribute to the wear process by: 1) abrading off the tribofilm as previously reported, [3,9] 2) impairing the tribofilm integrity as shown in Figures 6 and 7, and 3) promoting sulfidation in tribofilm formation. Qin et al showed the increase in sulfur utilization and enhancement of sulfidation upon addition of carbon during the high-temperature metal sulfidation process.…”
Section: Cb+zddp Causing Excess Wear On Tool Steelsmentioning
confidence: 60%
See 4 more Smart Citations
“…Carbon black may contribute to the wear process by: 1) abrading off the tribofilm as previously reported, [3,9] 2) impairing the tribofilm integrity as shown in Figures 6 and 7, and 3) promoting sulfidation in tribofilm formation. Qin et al showed the increase in sulfur utilization and enhancement of sulfidation upon addition of carbon during the high-temperature metal sulfidation process.…”
Section: Cb+zddp Causing Excess Wear On Tool Steelsmentioning
confidence: 60%
“…Such an antagonistic effect was later confirmed between soot extracted from used diesel engine oils and three types of phosphate‐based antiwear additives . In another report, interesting relationships were observed between wear rate and surface hardness in lubrication of an oil containing both CB and ZDDP in lubricating self‐mated AISI 52100 steel: the wear rates for the steel coupons with hardness HV ≤ 300 or ≥800 were significantly higher than those of intermediate hardness (HV = 400–600 HV) . The author attributed the increased wear on the softer steel (≤300 HV) as being due to the abrasion of surface/tribofilm by relatively hard CB particles (≈500 HV) whereas the higher wear rate of the harder steel (≥800 HV) was thought to be due to the increased high contact stress and frictional heating promoting tribochemical reactions.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations